Efficient Spectral-Galerkin Method and Analysis for Elliptic PDEs with Non-local Boundary Conditions - Hu, Lina; Ma, Lina; Shen, Jie (Journal of scientific computing, 2016)
We present an efficient Legendre–Galerkin method and its error analysis for a class of PDEs with non-local boundary conditions. We also present several numerical experiments, including the scattering problem from an open cavity, to demonstrate the accuracy and efficiency of the proposed method.